Fruit damages caused by the broad‐winged bush katydid, Scudderia pistillata (Orthoptera: Tettigoniidae) in commercial cranberry bog. (3rd September 2020) - Labarre, Didier; Piché‐Luneau, Samuel; Gervais, François; Légaré, Jean‐Philippe; Cormier, Daniel; Lucas, Eric
Abstract: In August 2018, unidentified damages were reported on cranberries in a conventional bog located in Quebec (Eastern Canada). Following a field inspection, high percentage of nibbled fruits as well as katydids (Orthoptera: Tettigoniidae) were observed. Several individuals (nymphs and adults) were seen feeding directly on the fruits. Specimens were captured and sent to the "Laboratoire d'expertise et de diagnostic en phytoprotection" of the "Quebec Ministry of Agriculture, Fisheries and Food" (LEDP‐MAPAQ). They were identified as Scudderia pistillata Brunner von Wattenwyl (Orthoptera: Tettigoniidae). Subsequently, a systematic fruit sampling was realized into the beds where damages were observed to assess spatial patterns of infestation. To our knowledge, it constitutes the first mention of significant damages associated to this species in cranberry bogs and, in some cases, up to 5% damages to the fruits were observed. This observation suggests that S. pistillata represents a potential pest for this crop. Additionally, a decrease of damage rates was observed when distancing from the north‐eastern corner of the bog. Hypothesis in regards of damages' spatial pattern is discussed.